2021
DOI: 10.3389/fimmu.2020.613815
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Governing Immunotherapy Resistance in Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a lethal malignancy with an overall 5-year survival rate of 10%. Disease lethality is due to late diagnosis, early metastasis and resistance to therapy, including immunotherapy. PDA creates a robust fibroinflammatory tumor microenvironment that contributes to immunotherapy resistance. While previously considered an immune privileged site, evidence demonstrates that in some cases tumor antigen-specific T cells infiltrate and preferentially accumulate in PDA and are cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 190 publications
(379 reference statements)
0
31
0
Order By: Relevance
“…Although immunotherapy has revolutionized the treatment of numerous types of cancer, there is no definitively positive result for PDAC patients 21 . PDAC is relatively resistant to chemotherapy or immunotherapy, mainly due to its characteristic TME with a fibrotic barrier formed by collagen, fibronectin, and hyaluronic acid, which prevents the delivery of sufficient chemodrugs and infiltration of immune effector cells 22 . The lack of NK and CD8 + T cells within the TME illustrates PDAC as a ‘cold’ tumour 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Although immunotherapy has revolutionized the treatment of numerous types of cancer, there is no definitively positive result for PDAC patients 21 . PDAC is relatively resistant to chemotherapy or immunotherapy, mainly due to its characteristic TME with a fibrotic barrier formed by collagen, fibronectin, and hyaluronic acid, which prevents the delivery of sufficient chemodrugs and infiltration of immune effector cells 22 . The lack of NK and CD8 + T cells within the TME illustrates PDAC as a ‘cold’ tumour 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated macrophages Tumor-associated macrophages (TAMs) are one of the most abundant immune cell populations in the pancreatic tumor stroma due in part to recruitment by oncogenic KRAS [163]. Either via direct tumorsignaling or via tumor-CAF crosstalk, TAMs are generally polarized to the immunosuppressive phenotype (M2) defined by Csf1R, CD206, and IL-10 expression along with reduced expression of MHC class II and Ly6C [155,164]. These M2 TAMs support tumorigenesis, immune escape (e.g., promoting Th2 cell differentiation), metastasis, and chemotherapeutic resistance [165].…”
Section: [Io Barrier] Immunosuppressive Cellular Tmementioning
confidence: 99%
“…The recruited and activated MAPK signalling pathway elements lead to the inflammation, apoptosis, proliferation, and carcinogenesis of pancreatic cells [ 39 ]. Increasing evidence has revealed that the infiltration and preferential accumulation of tumour antigen-specific T cells in PAAD are crucial to PAAD cell clearance and long-term remission [ 40 ].…”
Section: Discussionmentioning
confidence: 99%